Kekuatan Lembaga Manajemen Kolektif Nasional Dalam Penarikan Royalti - Annisa Putri Nadya (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Lately, there has been an issue regarding the management of royalties by LMKN, which has led to songwriters leaving the LMK membership and opting to manage their royalties independently. The goal of this study is to examine the role of LMKN in royalty collection and the relevant legal provisions governing it. The research method employed is a literature review focusing on LMKN's role in royalty collection. The findings of the study indicate that concerning the regulations on royalty collection, the state has stipulated them in the Copyright Law, PP56/2021, and Permenhuham9/2022. These regulations serve as supportive factors for enhancing royalty management in the commercialization of copyrighted works in the music field, aiming to manifest protection and legal assurance for creators. Furthermore, these provisions explicitly state that LMKN is the entity responsible for managing the royalties of songwriters. Therefore, songwriters cannot independently manage their royalties.